Viral infections and related fatal adverse events associated with complement inhibitors for PNH: a real-world pharmacovigilance analysis in FAERS - Zhong, Jinman; Chen, Chang; Xu, Yunman; He, Yueping; Tan, Jiewen; Xiong, Dan (Frontiers in Pharmacology, 2025)
BackgroundComplement inhibitors are increasingly utilized across various clinical indications, including the treatment of paroxysmal nocturnal hemoglobinuria (PNH). A thorough understanding of their adverse events (AEs) profiles, particularly regarding infections, is essential to ensure safe and effective treatment strategies.ObjectiveTo characterize the real-world AEs profile of complement inhibitors in PNH, with a focus on viral infections characteristics and distinct fatality risk, of while exploring potential implications for viral prophylaxis and identifying risk factors associated with fatal infection-related adverse events.MethodsComplement inhibitor-associated AE cases reported in FAERS between 2004 and 2024 were included. Pharmacovigilance analyses (including Reporting Odds Ratio [ROR] and multiple other metrics) were employed to detect signals for adverse events, including viral infection. Time-to-onset analysis and logistic regression were used to assess temporal patterns and identify factors associated with viral infections and fatal outcomes.ResultsAmong 58,613 AE reports, 11,957 (20.4%) were infection-related, and 8.91% were fatal. Infection-related AEs constituted 11,957 cases, predominantly linked to C5 inhibitors. Pharmacovigilance analysis revealed significant disproportionality signals for viral infections (e.g., influenza, herpes zoster, gastroenteritis viral, viral infection). C5 inhibitors had higher cases numbers, but C3 inhibitors demonstrated a stronger signal intensity (ROR = 3.52, 95%CI: 2.54–4.89). Fatal viral AEs had a median time-to-event of 12 days, while non-fatal viral infections occurred later, with a median time-to-event of 187 days. Older age, higher body weight, and treatment initiation in later quarters were associated with reduced viral infection risk, while female was linked to slightly elevated risk. While viral infections were common concomitant AEs, the fatality rate specifically for viral infections was lower compared to other complement inhibitor-associated AEs. Advanced age (≥75 years), treatment initiation in the third quarter and C5 inhibitor use were identified as significant risk factors for fatal infectious outcomes, whereas female sex and higher body weight appeared protective.ConclusionComplement inhibitors, particularly C3 agents, are associated with significant reporting of infectious AEs in FAERS, including specific viral infections like influenza and herpes. Early onset of viral AEs highlights the need for vigilance early in treatment. While advanced age and C5 use heighten mortality risk, the attenuated lethality of viral AEs suggests a distinct pathophysiological interplay warranting mechanistic study. The divergent risk profiles between C3 and C5 inhibitors underscore the need for personalized risk-benefit assessments in complement inhibition strategies.